NEOGRAPHY IN LINGUISTICS: THE ROLE OF NEOLOGISMS IN LANGUAGE DEVELOPMENT - Ergashev Tulkinjon Tukhtamurodovich (Modern American Journals, 2025)
The article explores the concept of "neography," a term coined half a century ago in linguistics to describe the field dedicated to recording and integrating newly emerged lexical units into dictionaries. Neography aims to document linguistic changes, standardize new words and phrases, and reflect their integration into a language. The development of neology and neography is closely tied to advancements in technology and science in the modern world, influencing fields such as automated text processing, machine translation, digitized speech, and computer-based education. Neologisms are not limited to scientific domains but also emerge in everyday life, journalism, and other areas. For instance, terms like coronavirus, Sputnik V, Pfizer, Moderna, and Sinopharm, introduced during the COVID-19 pandemic, became widely recognized in Uzbekistan due to their integration into daily life through health regulations.
Keywords: neography, neologisms, linguistics, lexicography, socio-political terminology, language development, dictionaries, communicative approach, language education, technology, semantic analysis, borrowed terms.